A Penerapan Pengelolaan Sumut Mobile dalam Menarik Minat Nasabah Bank Sumut Cabang Syariah Padangsidimpuan: A. implementasi Banking Pada Bank Sumut Cabang Syariah Padangsidimpuan atau Sumut Mobile - Seftia Fadillah Siregar Siregar; M. Yarham (Universitas Islam Negeri Mataram, 2023)
The presence of mobile nowadays makes financial management very easy and if we use it correctly we will experience enormous benefits. This can be seen by the Mobile Banking System which can help organized financial management, so that financial problems do not accour. Apart from that, using Mobile Banking can also make it easier to check account mutations, from which you can calculate how much funds you need. Apart from that, in checking mutations, there is also a processo fevaluating the result of budget recording within a certain period of time. So you will know about the budgets that have been set, such as with North Sumatera Mobile or Mobile Banking at Bank North Sumatera Syariah.